Regulation of expression and activity of the yeast transcription factor ADR1. - Blumberg, H (1988)
Disruption of ADR1, a positive regulatory gene in the yeast Saccharomyces cerevisiae, abolished derepression of ADH2 but did not affect glucose repression of ADH2 or cell viability. The ADR1 mRNA was 5 kilobases long and had an unusually long leader containing 509 nucleotides. ADR1 mRNA levels were regulated by the carbon source in a strain-dependent fashion. beta-Galactosidase levels measured in strains carrying an ADR1-lacZ gene fusion paralleled ADR1 and ADR1-lacZ mRNA levels, indicating a lack of translational regulation of ADR1 mRNA. ADH2 was regulated by the carbon source to the same extent in all strains examined and showed complete dependence on ADR1 as well. The expression of ADR1 mRNA and an ADR1-beta-galactosidase fusion protein during glucose repression suggested that the activity of the ADR1 protein is regulated at the posttranslational level to properly regulate ADH2 expression. The ADR1-beta-galactosidase fusion protein was able to activate ADH2 expression during glucose repression but showed significantly higher levels of activation upon derepression. A similar result was obtained when ADR1 was present on a multicopy plasmid. These results suggest that low-level expression of ADR1 is required to maintain glucose repression of ADH2 and are consistent with the hypothesis that ADR1 is regulated at the posttranslational level.